DIGITAL TRANSFORMATION IN COOPERATIVE BUSINESS PROCESSES: A STUDY ON COOPERATIVES IN THE GREATER BANDUNG AREA - Ratih Purbasari; Samún Jaja Raharja (Politeknik Negeri Bengkalis, 2022)
The importance of digital transformation in the 4.0 era requires business organizations to quickly adapt and change their business models in order to continue to survive and be able to compete. This also applies to cooperatives which not only operate as business organizations, but also bring socio-economic value. This study aims to analyze the digital transformation process by raising the locus of cooperatives in the Greater Bandung Region. This study uses mixed methods involving 40 cooperatives as respondents and 10 informants. Data was collected using a questionnaire and an interview process. The research data were analyzed descriptively by using a triangulation process. The results show that the digital transformation of cooperatives in the Greater Bandung area is in a good enough category but still needs to be improved. Future research can use different approaches such as the helix approach to map and analyze actors and their roles in the digital transformation process in cooperativesThe importance of digital transformation in the 4.0 era requires business organizations to quickly adapt and change their business models in order to continue to survive and be able to compete. This also applies to cooperatives which not only operate as business organizations, but also bring socio-economic value. This study aims to analyze the digital transformation process by raising the locus of cooperatives in the Greater Bandung Region. This study uses mixed methods involving 40 cooperatives as respondents and 10 informants. Data was collected using a questionnaire and an interview process. The research data were analyzed descriptively by using a triangulation process. The results show that the digital transformation of cooperatives in the Greater Bandung area is in a good enough category but still needs to be improved. Future research can use different approaches such as the helix approach to map and analyze actors and their roles in the digital transformation process in cooperatives.